Effects of N-terminus modified Hx-amides on DNA binding affinity, sequence specificity, cellular uptake, and gene expression. (1st September 2021) - Kiakos, Konstantinos; Satam, Vijay; Patil, Pravin C.; Sweers, Jeffrey; Bowerman, Michael; Tzou, Sam; Olsen, Kevin; Lee, Megan; Schaschl, Helmut; Keppler, Bernhard K.; Hochhauser, Daniel; Lee, Moses; et al.
Graphical abstract: Abstract: Five X-HxIP (Hx-amides) 6a-e, in which the N -terminus p -anisyl moiety is modified, were designed and synthesised with the purpose of optimising DNA binding, improving cellular uptake/nuclear penetration, and enhancing the modulation of the topoisomerase IIα ( TOP2A ) gene expression. The modifications include a fluorophenyl group and other heterocycles bearing different molecular shapes, size, and polarity. Like their parent compound HxIP 3, all five X-HxIP analogues bind preferentially to their cognate sequence 5′-TACGAT-3′, which is found embedded on the 5′ flank of the inverted CCAAT box-2 (ICB2) site in the TOP2A gene promoter, and inhibit protein complex binding. Interestingly, the 4-pyridyl analog 6a exhibits greater binding affinity for the target DNA sequence and abolishes the protein:ICB2 interaction in vitro, at a lower concentration, compared to the prototypical compound HxIP 3 . Analogues 6b-e, display improved DNA sequence specificity, but reduced binding affinity for the cognate sequence, relative to the unmodified HxIP 3, with polyamides 6b and 6e being the most sequence selective. However, unlike 3 and 6b, 6a was unable to enter cells, access the nucleus and thereby affect TOP2A gene expression in confluent human lung cancer cells. These results show that while DNA binding affinity and sequence selectivity are important, consideration of cellular uptake and concentration in the nucleus are critical when exerting biological activity is the desired outcome. By characterising the DNA binding, cellular uptake and gene regulatory properties of these small molecules, we can elucidate the determinants of the elicited biological activity, which can be impacted by even small structural modifications in the polyamide molecular design.